2014
DOI: 10.1038/ncomms4885
|View full text |Cite
|
Sign up to set email alerts
|

Microcephaly disease gene Wdr62 regulates mitotic progression of embryonic neural stem cells and brain size

Abstract: Human genetic studies have established a link between a class of centrosome proteins and microcephaly. Current studies of microcephaly focus on defective centrosome/spindle orientation. Mutations in WDR62 are associated with microcephaly and other cortical abnormalities in humans. Here we create a mouse model of Wdr62 deficiency and find that the mice exhibit reduced brain size due to decreased neural progenitor cells (NPCs). Wdr62 depleted cells show spindle instability, spindle assembly checkpoint (SAC) acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
218
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(238 citation statements)
references
References 36 publications
16
218
3
1
Order By: Relevance
“…[16][17][18] In support of a requirement for WDR62 in mammalian brain development, the depletion of WDR62 decreased mouse brain volume, reduced the proliferation of neural progenitor cells (NPCs) and increased spindle instability. 19,20 Similarly, in utero depletion of WDR62 in embryonic mouse brain also caused premature differentiation of NPCs into immature neurons. 19,21 In characterizing the mitotic functions of WDR62, the ectopic expression of mutant proteins recapitulating MCPH-associated gene changes resulted in perturbed localization to the spindle pole which suggests that the localization of WDR62 and its interacting partners at spindle poles is important for normal mitosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] In support of a requirement for WDR62 in mammalian brain development, the depletion of WDR62 decreased mouse brain volume, reduced the proliferation of neural progenitor cells (NPCs) and increased spindle instability. 19,20 Similarly, in utero depletion of WDR62 in embryonic mouse brain also caused premature differentiation of NPCs into immature neurons. 19,21 In characterizing the mitotic functions of WDR62, the ectopic expression of mutant proteins recapitulating MCPH-associated gene changes resulted in perturbed localization to the spindle pole which suggests that the localization of WDR62 and its interacting partners at spindle poles is important for normal mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] In the developing neocortex, mice compound heterozygous for AURKA and WDR62 had decreased brain size accompanied by increased mitotic index when compared to single heterozygous animals. 20 An analysis of mouse embryonic fibroblasts and neural progenitor cells from hypomorphic mutant mice with reduced WDR62 expression revealed decreased mitotic expression of AURKA and TPX2 suggesting a role for WDR62 in maintaining the mitotic activation of AURKA. 20 In contrast, the transient depletion of WDR62 in Hela cells did not alter AURKA activity and expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors adopted CRISPR technique to generate WDR62 ko AD293 cells and found in them the multipolar spindles, abnormal spindle morphology as reported for WDR62 knockdown and knockout in neuronal progenitors. 4,5 Interestingly, wildtype WDR62, but not those defective in AURKA-dependent phosphorylation can rescue the mitotic defects. In addition, AURKA mainly phosphorylates WDR62 at the N-terminal in M phase.…”
mentioning
confidence: 99%
“…1 Most primary autosomal recessive microcephaly-associated (MCPH) proteins including WDR62 are related to centrosome or spindle pole and essential for spindle pole formation and neurogenesis during brain development. [2][3][4][5] WDR62 is diffused in cytoplasm in the interphase and accumulates strongly at the spindle poles during mitosis. 2,3,5,6 Little is known regarding the mechanisms that determine the cell cycle-dependent spatiotemporal distribution of WDR62.…”
mentioning
confidence: 99%